Analyzing Structural and Physical Changes and the Future of Tehran’s Urban Fringe (The Case: The Fringe of District 22 of Tehran Municipality) - Taher Parizadi; Ali Shamaei (تحقیقات کاربردی علوم جغرافیایی, 2024)
The rapid growth of Tehran's population and the increasing need for land to respond to the needs of a residence, activity, urban services, etc., caused cities caused the city to move forward in its surrounding lands and changed land uses significantly and quickly. This paper aimed to investigate these changes and their futures in district 22 of Tehran Municipality. It has a descriptive-analytical method and the data is obtained from documentary and library sources. The process of changes and the existing situation were analyzed qualitatively and descriptively. To identify the drivers of future changes, a structural-interpretive model has been implemented using Mic-Mac software. For this purpose, all the land uses and activities (64 land uses and activities) were extracted and listed. Then, by implementing the Delphi method with the participation of 8 experts, 25 possible land uses were determined. After completing the matrix, the nearest rounded figures to the average numbers which were inserted by the experts, are the basis of the analysis. Finding showed that before the formation of the district, in 1972, the urban fringe of the district, large-scale urban land uses such as sports, research-educational, recreational and military land use, as well as urban and residential complexes, established in agricultural and vacant lands.  Then, constructed settlements, parks, and green spaces as well as recreational, military, research-educational lands and roads, were established here. The analysis of drivers also showed that in the future, out of a total of 25 possible land uses, forestry, eco- tourism, constructiing villas and secon homes, parks, malls, military spaces, stadiums and sports places, and roads and transportation terminals cause to main changes on the structural-physical of the studied fringe.